Christ on a donkey Palm Sunday, triumphal entries, and blasphemous pageants - Harris, Max 1949- (Early social performance, 2019)
‹I›Christ on a Donkey‹/I› reveals Palm Sunday processions and related royal entries as both processional theatre and highly charged interpretations of the biblical narrative. Harris’s narrative ranges from ancient Jerusalem to modern-day Bolivia, from veneration to iconoclasm, and from Christ to Ivan the Terrible. A curious theme emerges: those representations of Christ’s entry into Jerusalem that were labelled blasphemous or idolatrous by those in power were most faithful to the biblical narrative of Palm Sunday, while those that exalted power and celebrated military triumph were arguably blasphemous pageants